The political psychology of extremism; 'naturalness' of the phenomenon in the Western Balkans - Hadžić, Faruk (Technium Social Sciences Journal, 2020)
In a symbolic sense, this region may be burdened with a kind of negative ontology that is very difficult to change. Extremist ideologies are, in fact, just a continuation of the war by other means. They have entered education, and beginning to metastasize and affect the entire social tissue, becoming "naturalness", supported by different mythopoetic narratives of a particular nation. In an environment where politics is extreme, many avoid concerns the very nature of extremism and the process of radicalization within the discourse of "peacetime" extremism. Extremism stems from finding two basic human needs: the need for cognitive closure and personal significance. Subordination of the individual to the national community, i.e., the leader, is a psychological form of political behavior marked by an obsessive preoccupation with the decline of the community; sacrificing the process of compensatory, the cult of unification while abandoning democratic freedoms with redemptive violence and, regardless of moral and legal constraints, seeks to achieve ethnoreligious threatening collectivity (tribal identity). Extremism uses the properties of consciousness: ethnicity, religiousness, and thinking in absolute categories (in a destructive aspect to add naturalness to its ideas) to justify activities with a sacred or "patriotic" will. Although the violent potential of nationalism in the Balkans should be overlooked by no means, the inflammatory rhetoric is just a method used by political elites to manipulate the public.